2016
DOI: 10.4238/gmr.15038556
|View full text |Cite
|
Sign up to set email alerts
|

Balanced reciprocal translocation at amniocentesis: cytogenetic detection and implications for genetic counseling

Abstract: ABSTRACT. Balanced translocation is a common structural chromosomal rearrangement in humans. Carriers can be phenotypically normal but have an increased risk of pregnancy loss, fetal death, and the transmission of chromosomal abnormalities to their offspring. Existing prenatal screening technologies and diagnostic procedures fail to detect balanced translocation, so genetic counseling for carriers remains a challenge. Here, we report the characteristics of chromosomal reciprocal translocation in 3807 amniocent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
1
5
0
1
Order By: Relevance
“…Reciprocal translocation is a type of chromosome rearrangement that is involved in the exchange of chromosome segments between two chromosomes that do not belong to the same pair of chromosomes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Reciprocal translocation is a type of chromosome rearrangement that is involved in the exchange of chromosome segments between two chromosomes that do not belong to the same pair of chromosomes [14].…”
Section: Introductionmentioning
confidence: 99%
“…[52] In our study, we identifi ed three breakpoints of de novo BCR not reported previously by these authors. [51,52] These three breakpoints (3q13.1, 3q13.2, and 9p12) were not reported in the large-scale studies by Warburton and Giardino, [5,7] in studies in Asia, [9][10][11] or in other studies with smaller sample sizes conducted in Europe, North America and Australia. [12,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] Rosenberg studied 1056 individuals from 52 populations and found that most genetic variation was within populations; only 3%-5% of genetic variation was due to major group differences.…”
Section: Discussionmentioning
confidence: 85%
“…[45,46] We found many reported breakpoints in other antenatally diagnosed de novo BCR studies, but we also found eight breakpoints that previous studies did not identify. [5,7,[9][10][11][12][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] All those studies primarily included Caucasian and Asian populations, and the majority, as in this study, used cytogenetic banding methods to analyze breakpoints.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations